Three new sesquiterpenes from Ainsliaea glabra. Issue 2 (17th January 2019) - Chen, Ya-Ping; Tong, Cui; Lu, Wen-Quan; Shen, Yun-Heng; Wu, Zhi-Jun; Chen, Wan-Sheng
Abstract: Three new sesquiterpenes: 4-acrylic-6-methyl-α-tetralone (1 ), ainsliaea acid A (2 ) and ainsliaea acid B (3 ), together with 8 known compounds(4-11 ) were isolated from the whole herb of Ainsliaea glabra and their structures were established by means of 1D and 2D NMR spectroscopy and HR-ESIMS. Compounds1–6 were tested for the inhibition of nuclear factor kappa B (NF-κB) in the 293-NF-κB-luciferase reporter cell line induced by lipopolysaccharide (LPS), and compound2 was further tested for the production of tumor necrosis factor- α (TNF- α ), interleukin-1 β (IL-1 β ), IL-6 and IL-10 in RAW264.7 macrophages induced by LPS. The isolated compound2 exhibited significant anti-inflammatory activity. Abstract :